Transboundary Pollution and Welfare Effects of Technology Transfer - Yasuhiro Takarada (European Regional Science Association (ERSA), 2004)
The purpose of this paper is to examine the welfare effects of pollution abatement technology transfer in a two-good two-country model with transboundary pollution. In each country, one industry emits pollution as a joint product of output and the sum of domestic and cross-border pollution decreases productivity of the other industry. Then, we show that technology transfer can bene?t the recipient country regardless of the level of cross-border pollution. Moreover, the donor country gains from technology transfer if all pollution is transboundary but it may harm the donor country with out cross-border pollution. We demonstrate that the effects of technology transfer depend on the trade pattern as well as cross-border pollution. Keywords: Environment; Pollution; Technology transfer; Pareto-improving transfer JEL classi?cation: D62; F18; O39
Keywords: D62; F18; O39; 330; Environment; Pollution; Technology transfer; Pareto improving transfer